15 Years of Moss Biomonitoring for Air Quality Assessment in Albania - Pranvera Lazo; Sonila Shehu Kane; Flora Qarri; Shaniko Allajbeu; Lirim Bekteshi (Aerosol and Air Quality Research)
Abstract The characterization of chemicals in atmospheric deposition is essential for the assessment of air quality. The purpose of this research is to investigate the spatial patterns and temporal trends of trace metals, identify emission pathways, and evaluate the most likely influences on concentration levels throughout the entire territory of Albania. Hypnum cupressiforme moss species were collected from 75 locations and used as a biomonitor of trace metals in atmospheric deposition. To evaluate the spatiotemporal trend and related processes of hazardous chemicals in the air, the concentrations data of elements from moss surveys conducted in 2010, 2015, and 2021 was statistically analyzed using multivariate analysis, descriptive statistics, data transformation, and geographical mapping. The results of the statistical analysis revealed that the metal processing and extraction sectors were the primary local emission sources, which caused the variation in the concentration of metals in moss samples. The spatial distribution of trace metals showed a high fluctuation in time and space, with a tendency toward an enhancement in elements derived from anthropogenic and soil dust emission sources. The pollution levels have remained constant throughout the entire monitoring period without any notable shifts. Due to the high background levels of most elements, enrichment factors revealed no to slight enrichment in more than 80 percent of the territory. The obtained data can help understanding and assessing the level of air pollution and implementing an effective strategy for clean air.